Stability Analysis of Islamic Banks Using The RGEC Method Against The Risk of Financial Distress as a Pillar of The Halal Economy in Indonesia - Nur Ali, Nurfadilla; Mustamin, Asyraf; Kamaruddin; Tamrin, Saenal (Likuid Jurnal Ekonomi Industri Halal, 2025)
This study aims to analyze the effect of the health level of Islamic Banks as measured by the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) on the possibility of financial distress. The background of this research is based on global economic uncertainty during the 2019-2023 period and the increasing Non Performing Financing (NPF) and BOPO ratios at Islamic Banks, which indicate potential vulnerability to financial distress. This research uses a descriptive quantitative approach with purposive sampling technique of Islamic Commercial Banks listed on the Indonesia Stock Exchange for the period 2021-2024. The data analysis technique includes ranking the RGEC ratio, classical assumption test, and multiple linear regression analysis with the help of SPSS 22 software. The results showed that simultaneously, all RGEC components had a significant effect on financial distress with an F value of 11,596 and a significance of 0.000 and an adjusted R² of 0.672. Partially, the Risk Profile variable measured through NPF (p = 0.012) and FDR (p = 0.002), as well as the Capital variable (CAR) with a significance of 0.000 have a positive and significant effect. Meanwhile, the Good Corporate Governance and Earnings variables (ROA, ROE, and NOM) did not show a significant effect. Thus, it can be concluded that although simultaneously RGEC affects financial distress, partially only Risk Profile and Capital have a significant influence. This finding underscores the importance of strengthening financing risk management and capital in maintaining the financial stability of Islamic banks amid economic dynamics. The implication of this research is as one of the information tools in general for related parties and especially for Islamic bank companies listed on the IDX to maximize risk management, capital strength, managerial strategies, and policy improvements.